Evaluation of in vitro Anti-cancer Activity of Linum usitatissimum and Mentha spicata Combination Extract against MCF7 Breast Cancer Cell-line - T, Ashwini; I, Glory Josephine; Elizabeth, Arul Amutha (Indian Journal of Pharmaceutical Education and Research, 2024)
Background/Aim: Breast cancer is one of the most common cancers among women in India. Though the current treatment is beneficial, it is complicated with lots of risks and disadvantages. So, the search for alternatives especially phytochemicals is increasing recently. Linum usitatissimum (Flaxseed) and Mentha spicata (Spearmint) are plant-based products, which are known for their various health benefits, exhibited anticancer activities independently in vitro. With the Proven importance of drug synergism, it is hypothesized that a combination of products would exhibit synergistic activity. Objectives: The present study aimed at evaluating the anticancer activity of a combination extract of Linum usitatissimum and Mentha spicata at MCF7 breast cancer cell line using MTT Assay. Materials and Methods: A combination methanolic extract of Linum usitatissimum and Mentha spicata was added to the MCF7 cell line at different concentrations ranging from 20 to 100 μg/mL. The IC50 value was calculated based on the percentage of inhibition. Results: Cell viability decreased to 24.6% at the maximum measured concentration of 100 μg/mL. The IC50 value was found to be at 70 μg/mL. Conclusion: Our study results showed that there is a significant anticancer property in combination extract of Linum usitatissimum and Mentha spicata in a concentration-dependent manner in vitro.
Keywords: Anti-cancer activity; Flaxseed; Spearmint; Breast cancer; MTT assay